Financial market integration under EMU - Jappelli, Tulio; Pagano, Marco; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
The European Monetary Union (EMU) has been the single most important policy-induced innovation in the international financial system since the collapse of the Bretton-Woods system. By eliminating exchange rate risk, EMU has eliminated a key obstacle to financial integration. But while a single currency is a necessary condition for the emergence of pan-European capital markets, it is not a sufficient one. Other frictions may still stand in the way of full integration: persistent differences in regulations applying to financial intermediaries, tax treatment, standard contractual clauses and business conventions, issuance policy, security trading systems, settlement systems, availability of information, and judicial enforcement may still segment financial markets along national borders. In the process that preceded and accompanied the introduction of the euro, however, monetary unification triggered a sequence of policy actions and private sector responses that swept aside many other regulatory barriers to financial integration. To what extent has this process of regulatory reform led to actual financial integration? And if European financial markets have actually become more integrated, to what extent have these changes spurred growth and investment in Europe? Will financial integration affect also the ability of households to shoulder risks, or the ability of European economies to adjust to macroeconomic shocks? Which policy lessons can we draw for the future of European financial markets?
Economic Papers